Shorter waiting times from education to colonoscopy can improve the quality of bowel preparation: A randomized controlled trial - Lee, Jin; Kim, Tae Oh; Seo, Joo Wan; Choi, Joon Hyuk; Heo, Nae-Yun; Park, Jongha; Park, Seung Ha; Yang, Sung Yeon; Moon, Young Soo (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Adequate bowel preparation is essential for an effective and safe colonoscopy. This study aimed to evaluate the quality of bowel preparation according to waiting times from education to colonoscopy. Materials and Methods: A prospective, investigator-blinded, randomized study was performed from December 2016 to March 2017. Patients were divided into two groups: within 2 weeks (group A, n=64) or more than 2 weeks (group B, n=66) from education about bowel preparation to colonoscopy. The primary outcome was the quality of bowel preparation as assessed by the Boston Bowel Preparation Scale (BBPS). The secondary outcome was the polyp and adenoma detection rate. Results: A total of 130 patients were enrolled. The total BBPS score was significantly higher in group A (within 2 weeks from education to colonoscopy) than in group B (more than 2 weeks). Total BBPS scores were 8.25±0.97 in group A and 7.75±1.32 in group B (P=.017). The rate of good preparation (BBPS≥8) was higher in group A than in group B (78.1% vs. 59.1%, P=.020). The rates of polyp and adenoma detection were both slightly higher in group A (polyps, 42.2% vs. 38.5%, P=.667; adenoma, 31.2% vs. 22.7%, P=.275). A numerical trend was observed for the slightly superior polyp and adenoma detection rate in group A, but it was not statistically significant. Conclusion: This study demonstrated that shorter waiting times from education to colonoscopy can improve the quality of bowel preparation. Ensuring sufficient staff and equipment for endoscopy is one approach to reducing waiting times to colonoscopy. If waiting times can not be reduced, more contact through telephone, e-mail, and text messaging could be used to remind patients about information regarding bowel preparation. Cite this article as: Lee J, Kim TO, Seo JW, et al. Shorter waiting times from education to colonoscopy can improve the quality of bowel preparation: A randomized controlled trial. Turk J Gastroenterol 2018; 29: 71-7.